RUMINAL IMPACTION DUE TO PLASTIC FOREIGN BODY IN GIR COW - Suthar , D N; Patel , J B (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Surgical affections of the ruminant fore stomach due to ingested foreign bodies are the subject of attention almost all over the world and of major economic importance due to severe loss of production and production ability and sometimes death of the animal. Now a days problem of non-penetrating foreign body syndrome is increasing at alarming pace in urban areas where the animals are let loose for free grazing. It is characterized by accumulation of plastic, rexin, polythene bags, ropes and metal objects like nuts, bolts etc. in the rumen and reticulum of bovine (Dandge, 1993). The present paper report successful surgical management of case of ruminal impaction due to plastic foreign body in Gir cow.
Keywords: RUMINAL; GIR COW; PLASTIC